Elastic modulus of hyaluronic acid hydrogels by compression testing - Rachel Lee; Emily K. Hall; Bassam A. Aljohani; Jake McClements; Marloes Peeters; Mark Geoghegan (Journal of Materials Science: Materials in Medicine)
Abstract Hyaluronic acid was crosslinked using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to form hydrogels with low elastic modulus. These hydrogels were swollen in water and the elastic modulus was obtained with a contact mechanics approach in ambient conditions using a low-load mechanical tester under compression. The modulus was measured during both the approach and retraction of the cylindrical probe into the gel and was found to be of the order of 30 kPa. The modulus was also measured from a stress-strain curve (47 kPa), in reasonable agreement with the contact mechanics approach. However, nanoindentation and rheology measurements reveal much smaller moduli, indicating that the technique used interrogates different length scales within the gel. This has profound implications for the applications of hydrogels used, for example, in tissue engineering. The values reported here are likely to be appropriate for applications where contact with the spinal cord is necessary. It is argued that a contact mechanics approach is appropriate for the characterization of hydrogels for applications designed for contact with tissue. Graphical Abstract